Inovasi media pembelajaran prasekolah melalui pelatihan aplikasi Canva dalam pembuatan Worksheet: Innovation of Preschool Learning Media through Canva Application Training in Worksheet Creation - Yuniarti (ABSYARA: Jurnal Pengabdian Pada Masayarakat, 2024)
Preschool education plays a crucial role in laying the foundation for children's development before entering formal education. Children need a conducive environment and appropriate teaching methods to acquire basic knowledge, skills, and understanding essential for their growth. Teachers at IGABA-Kindergarten Kuburaya play a central role in providing quality education to preschool children. In the digital era, information technology has become an integral part of daily life, including education. Canva, a graphic design and visual presentation application, has untapped potential for creating worksheets and learning materials for preschool children. Previously, IGABA Preschool Kuburaya faced challenges such as limited resources, inadequate digital skills among teachers, and low student engagement, which hindered effective learning processes. This study aims to train preschool teachers in Kuburaya to use Canva effectively in their teaching. The program, conducted from May to June 2023, included three main activities: Canva usage training, practical sessions, and evaluation. The training was attended by 30 preschool teachers. Participant satisfaction surveys showed high satisfaction levels: 95.7% found the material highly relevant to their needs, 95.7% found it easy to understand and apply, and 92.33% noted the material was presented clearly and systematically. Additionally, 86.67% felt the trainers were knowledgeable, 83.33% appreciated the opportunity for Q&A, and 90% found the trainers presented the material clearly and sequentially. Evaluation results indicated significant improvements in teachers' digital skills and the quality of the learning materials they produced. This program positively impacted preschool education in Kuburaya, enhancing teachers' competencies and creating more engaging learning environments for children